Human Initiative Movement: Enhancing Environmental Literacy and Awareness among Orphans in Bengkulu City - Yogopriyatno, Jatmiko; Nur Hasanah, Widya (Asian Journal of Environmental Research, 2024)
This paper examines the Human Initiative organization in Indonesia and its efforts to provide education for orphans in Bengkulu City. It analyzes the organization's resource mobilization using various data collection techniques. Establishing an education center called the Home of Learning is seen as a social movement that successfully achieved its goals. The research considers five aspects proposed by Oberscall: social movement organization, leaders and leadership, resources and resource mobilization, networks and participation, and community opportunities and capacity. The research findings show that (Home of Learning) HOME in Bengkulu is a social movement that effectively implements quality education programs. This success is due to a clear institutional structure, effective leadership, resource mobilization, community participation, and opportunities for child development. Overall, this research highlights the effectiveness of the Human Initiative in providing education for orphaned children.